Characteristics investigation of single-sided ironless pmlsm based on halbach array for medium-speed Maglev train - Zhihua Zhang; Liming Shi; Ke Wang; Yaohua Li (CES Transactions on Electrical Machines and Systems, 2017)
This paper investigates characteristics of ironless permanent magnet linear synchronous motor (PMLSM) based on Halbach array used for medium-speed (200km/h) maglev train. Long primary ironless coil is laid in the middle of track and the Halbach permanent magnet array is attached to the bottom of each bogie as a source of traction, U-shape electromagnets at the both sides of the train for levitation. Two dimensional analytical model of single-sided ironless PMLSM based on Halbach array is established, using linear overlay method, the no-load air gap magnetic field is calculated firstly, winding current density distribution is obtained for calculating the characteristics of thrust and normal force against power angle, including force characteristics with equal and unequal pole pitch, the influence of steel sleeper, etc. Besides, the mathematical model for this type motor is built by 3D finite element method, the traction characteristics of medium-speed maglev under maximum speed 200km/h are calculated. The characteristics of this type motor are satisfactory owing to there is no detent force in the motor and thrust force reach maximum meanwhile normal force can be eliminated. Calculation method is verified by comparing finite element results, experimental result on a 200kW type motor further validates the accuracy of calculation and some important conclusions are obtained.